Membrane Association of Conjugally Transferred Deoxyribonucleic Acid in Escherichia coli Minicells - Shull, Fred W. (1971)
The conjugally acquired deoxyribonucleic acid (DNA) of small, anucleate cells (“minicells”) of a mutant strain of Escherichia coli K-12 was found to be predominantly associated with the bacterial membrane. Evidence from X-irradiation studies in vivo shows that there is no decrease in DNA-membrane association under conditions which reduce the DNA to one-sixth its original size and suggests the possibility of multiple DNA-membrane association sites. Preliminary enzymatic studies indicate the involvement of protein, DNA, and lipids in the membrane association of the DNA.